Role of personal characteristics and intrinsic motivation on the creative performance of private university officers in Bangladesh: A conceptual analysis - Mahfuzur Rahman, Md.; Abdul Mutalib @Taib, Mahazan; Aktaruzzaman Khan, Mohammad (Edelweiss Applied Science and Technology, 2024)
In rapidly changing environment, creativity is not only necessary for competitive advantage but is also contributing to organizational innovation, effectiveness, and survival. The study aims at uncovering the role of personal characteristics and intrinsic motivation on the creative performance of private university officers in Bangladesh. The present study is descriptive and conceptual and uses secondary data taken from different journals, books, and research articles (both theoretical and empirical). The findings show that role of personal characteristics and intrinsic motivation in the creative performance of private university officers in Bangladesh. Management of private universities, HR specialists, and policy-makers can utilize the findings of this study to ensure the creative-performance of their employees for the sake of facing the challenges and reaching the goals.